Theoretical framework of life circles in Chinese small towns and the optimization of spatial layout for public service facilities based on residents' distance sensitivity. - Wang, Yue; Xie, Haihui; Hua, Yi; Jin, Bo; Qiu, Zhi (Humanities & Social Sciences Communications, 2024)
Due to China's rapid urbanization, its residential areas and the residents in small towns exhibit dual and complex urbanization patterns and characteristics. The relevant national standards currently do not provide detailed guidance regarding the planning and construction of public service facilities and have failed to address the complexities of human–land urbanization patterns. Their "one-size-fits-all" approach toward facility programming has resulted in misalignment of facility supply and demand and in poor accessibility of public service facilities. As a result, many existing facilities are not used; frequently, facilities not included in the public service system are used, resulting in inefficient usage. Previously, the authors have investigated the functional programming of facilities, proposing a "required + optional item" public service facility guidance-control system based on the actual needs of residents, which addresses the issue of what types of facilities should be provided to residents. Building upon prior research, this study focuses on the spatial layout of facilities and explores the logic of suitable life circle planning in small towns in China. Specifically, this study extracts indicators such as tolerance distance, usage frequency, and functional demand to assess residents' "distance sensitivity" in accessing facilities. It uncovers the differentiated characteristics of distance sensitivity among residents at different stages of urbanization regarding rural and non-rural facilities. The study proposes the determining principles for a life circle–layered partitioning mode in small towns and develops a model framework for suitable life circle. It defines the life circle partitioning and layers for residents at different stages of urbanization. Based on this framework, this study establishes a fundamental principle for preventing dissatisfaction among residents with low service expectations, proposing a "basic assurance + optimization enhancement" plan for life circle layers in rural- and urban-biased residential areas. This study addresses the uneven urbanization levels within small towns, revealing the spatial hierarchical relationships between facilities in urban- and rural-biased residential areas. Guided by the principle of "control + guidance," it aims to offer local policymakers more flexibility, clarifying and correcting past "one-size-fits-all" approaches to facility planning. The goal is to elevate the standard of public services in small towns by providing methods of optimization and theoretical foundations for renewal practices and the refinement of construction-related regulations.